Insight into the mechanical properties and the sustainable application of recycled permeable concrete: Green low-carbon concrete technology - Shaojian Xia; Lei Peng; Wu Zhang; Hongliang Zhu; Jing Li (PLoS ONE, 2025)
The performance optimization of reclaimed permeable concrete helps to reduce the energy consumption of building materials preparation and promotes green and sustainable development. To further adjust the ratio of reclaimed permeable concrete and optimize the mechanical properties of reclaimed permeable concrete, the influence of aggregate particle size distribution on the mechanical properties of reclaimed permeable concrete is analyzed. In the analysis of the effect of particle size distribution on the mechanical properties of recycled aggregate permeable concrete, the design experiment was examined. The experiment showed that when the water-cement ratio was 0.28/0.30/0.32 and the porosity was 10%, the increase in permeability coefficient was 28.1%/50.9%/29.0%. When the recycled permeable concrete had a water-cement ratio of 0.30 and a particle grading of 8:2 at a target porosity of 10%, the average permeability coefficient was the lowest, only 1.23mm/s. The circulating permeable concrete of the study design met the requirement of the permeability coefficient under the CJJ/T1352009 standard, which was not less than 1 mm/s. The extant research on the influence of aggregate grading and other parameters on the performance of recycled permeable concrete indicates that the ratio of recycled aggregate permeable concrete can be optimized. Furthermore, the customization of concrete ratio according to the needs of different buildings can effectively reduce the manufacturing cost of building materials.